A proposed model to reduce the impacts of educide on school education in Gaza Strip during the 2023 war - Alghirbawi, Bahaa Darwish (Journal of Educational and Psychological Sciences, 2025)
The study aimed to design a proposed model to reduce the impacts of educide on school education in Gaza Strip during the 2023 war. To achieve the study’s objective, the researcher used the analytical descriptive approach and designed an electronic questionnaire to identify the degree to which the study sample members assessed the impacts of educide on school education in Gaza Strip. The questionnaire consisted of (54) items, divided into (6) main domains: (learning and teaching, school environment, teachers, students, school administration, parents and the local community). The study sample consisted of (379) teachers, who were selected using a simple random method. The results of the study showed that the mean of the study sample’s assessment of the impacts of educide on school education in Gaza Strip was (4.556), with a relative weight of (91.13%), and a very high degree. It also showed no statistically significant differences at the (α≤0.05) level between the mean scores of the study sample’s assessments of the impacts of educide on school education in Gaza Strip attributable to variables (gender, educational qualification, and place of work). In light of the study’s results, the researcher designed a proposed model that includes suggestions for reducing the impacts of educide on school education in Gaza Strip. The researcher recommended adopting a comprehensive plan to save education, adopting blended education, allocating programs to compensate for students’ educational and value losses, and implementing programs to support the psychological and social aspects of students and teachers.